1982
DOI: 10.1172/jci110635
|View full text |Cite
|
Sign up to set email alerts
|

Bence Jones proteins and light chains of immunoglobulins. Preferential association of the V lambda VI subgroup of human light chains with amyloidosis AL (lambda).

Abstract: A B S T R A C T An antiserum prepared against a ABence Jones protein from a patient (SUT) who had multiple myeloma and amyloidosis had specificity for X-light chains of the chemically defined variable (V) region X-chain subgroup XVI. Sequence analyses of protein SUT and of five other X-light chains recognized immunologically as of the VAVI subgroup revealed that all six proteins had the N-terminal sequence characteristic for prototype XVI proteins. The isotypic nature of the VAVI subgroup was demonstrated immu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
87
0
3

Year Published

1983
1983
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 236 publications
(93 citation statements)
references
References 17 publications
1
87
0
3
Order By: Relevance
“…5,6 AL amyloidosis is a clonal plasma cell disorder in which extracellular fibrillar amyloid protein deposits composed primarily of immunoglobulin light chains accumulate in tissues. [7][8][9] Although some patients can present with AL amyloidosis and multiple myeloma, in most AL amyloidosis patients, the burden of clonal plasma cells in the bone marrow is comparatively low and diagnostic criteria of myeloma are usually absent. Unlike in myeloma, AL amyloidosis patients typically present with cardiac, renal, hepatic, gastrointestinal and/or neuropathic disease due to accumulation of amyloid fibrils.…”
mentioning
confidence: 99%
“…5,6 AL amyloidosis is a clonal plasma cell disorder in which extracellular fibrillar amyloid protein deposits composed primarily of immunoglobulin light chains accumulate in tissues. [7][8][9] Although some patients can present with AL amyloidosis and multiple myeloma, in most AL amyloidosis patients, the burden of clonal plasma cells in the bone marrow is comparatively low and diagnostic criteria of myeloma are usually absent. Unlike in myeloma, AL amyloidosis patients typically present with cardiac, renal, hepatic, gastrointestinal and/or neuropathic disease due to accumulation of amyloid fibrils.…”
mentioning
confidence: 99%
“…Together these genes accounted for up to 42% of amyloid light chains. The preferential association of VI (6a) light chains with amyloidosis is well established by the pioneering studies of Solomon et al 6 in the early 1980s. Subsequent work using protein sequencing unequivocally demonstrated that virtually all VI monoclonal light chains isolated so far are from amyloidosis patients.…”
Section: Figure 5 Somatic Mutations In Amyloid and Polyclonal V Regimentioning
confidence: 89%
“…2,5 These observations suggest the existence of V genes with a propensity to form amyloid (amyloidogenic). Indeed, light-chain protein sequencing 6 and enzyme-linked immunosorbent assay (ELISA) typing 7 showed a very high prevalence of VI family light chains in amyloidosis and a strong association with this disorder: with rare exceptions, VI monoclonal light chains are found only in patients with AL. Since this seminal observation, no other amyloid-associated genes have been identified.…”
Section: Introductionmentioning
confidence: 99%
“…l LCs are 2-3 times more commonly associated with AL-amyloidosis than k LCs. 15 Solomon et al 16 have reported that l VI LCs are more specifically associated with amyloidosis. Corroborating evidence has been provided by Comenzo et al 17 demonstrating a striking tropism of the lVI LCs for glomerular amyloidosis.…”
mentioning
confidence: 99%